From civic to administrative centres. An idea of the publicness in Colombian governmental architecture, 1960-1975 - William García Ramírez; Mateo Franco Grimaldo (Dearq, 2022)
The purpose of this research was to investigate the idea of publicness embodied by governmental architecture in Colombia after 1960. In principle, the results show a disparity between the conceptualisation of architectures conceived under the idea of ​​Civic Centres and their effective construction as Administrative Centres. An exception of the above is the National University of Colombia’s civic centre, a project that is seldom recognized as such.